No Useless Mouth Waging War and Fighting Hunger in the American Revolution - Herrmann, Rachel B.; Project Muse. (Cornell University Press, 2019)
"Argues that Native American and formerly enslaved communities lost the fight against hunger because white officials in the United States, Nova Scotia, and Sierra Leone curtailed the abilities of men and women to fight hunger on their own terms"--
Introduction : why the fight against hunger mattered -- Hunger, accommodation, and violence in colonial America -- Iroquois food diplomacy in the revolutionary North -- Cherokee and Creek victual warfare in the revolutionary South -- Black victual warriors and hunger creation -- Fighting hunger, fearing violence after the Revolutionary War -- Learning from restrictive food laws in Nova Scotia -- Victual imperialism and U.S. Indian policy -- Black loyalist hunger prevention in Sierra Leone -- Conclusion : why native and black revolutionaries lost the fight.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sierra Leone -- History -- To 1896.; Nova Scotia -- History -- 1763-1867.; United States -- History -- Revolution, 1775-1783 -- African Americans; United States -- History -- Revolution, 1775-1783 -- Indians; African Americans -- Food -- History -- 18th century; Indians of North America -- Food -- History -- 18th century; Food security -- Sierra Leone -- History -- 18th century; Food security -- Nova Scotia -- History -- 18th century; Food security -- United States -- History -- 18th century; Electronic books